Effect of heating methods and immersion times on the physicochemical properties of polyimide based on 3,3′,4,4′-benzophenone tetracarboxylic dianhydride and 4,4′-methylene diphenyl diisocyanate (BTDA-MDI) - Nur Shawalina Azran; Najaa Mustaffa; Nadhratun Naiim Mobarak (Penerbit Universiti Kebangsaan Malaysia, 2025)
Aromatic polyimides (PIs) derived from diisocyanates can be synthesized through one-step polycondensation process, either by stepwise heating with controlled temperature increments or by direct heating, in which the reaction mixture is exposed immediately to the final target temperature. However, the impact of these heating method on the resulting PIs properties remains underexplored. In this study, PIs were synthesized from the reaction of 3,3′,4,4′-benzophenone tetracarboxylic dianhydride (BTDA) and 4,4′-methylene diphenyl diisocyanate (MDI) using both heating methods. Additionally, the effect of longer and shorter immersion times in distilled water applied after the thermal reaction during the precipitation process was examined to determine their influence on polymer properties. The combined effects of heating protocol and immersion duration on precipitation behaviour, solubility, and thermal stability were evaluated. Structural characterization was performed using FTIR and NMR spectroscopy. Thermogravimetric analysis (TGA) confirmed high thermal stability, with degradation temperatures ranging from 574 °C to 585 °C. Solubility tests showed that all BTDA-MDI-based PIs were partially soluble in N-methyl-2-pyrrolidone (NMP), while a comparative PIs synthesized from 6FDA-MDI was fully soluble in various organic solvents. These findings suggest that monomer structure has a stronger influence on solubility than on thermal or crystalline properties. Overall, the study provides valuable insights into how synthesis and post-reaction conditions influence PIs characteristics, supporting their optimization for advanced material applications.